Tectonics of Enceladus’ South Pole: Block Rotation of the Tiger Stripes - Rossi C.; Cianfarra P.; Salvini F.; Bourgeois O.; Tobie G. (Journal of Geophysical Research: Planets, 2020)
The South Polar Terrain (SPT) of Enceladus is a site with eruptions of gas and water ice particle plumes, which indicate internal geodynamic activity. These eruptions are located along a series of tectonic structures, that is, the Tiger Stripe Fractures (TSF), which are composed of regularly spaced, linear depressions. The SPT is surrounded by sinuous chains of ridges and troughs (the Marginal Zone). To unravel the tectonics that affect the region and its evolution, we performed specific structural mapping and quantitative analyses of brittle features from remotely sensed images. The results are consistent with a block rotation model, in which several tectonic regimes coexist. The TSF are left-lateral strike-slip faults that bound rigid elongated blocks. The blocks rotate clockwise and are enclosed in a regional scale right-lateral kinematic framework expressed in the Marginal Zone. These two opposite and complementary kinematic regimes induce transtensional and transpressional regimes within the SPT. An evolutionary tectonic model is proposed for the past and future evolution of the SPT. This model confirms the role of tectonic-related kinematics in icy satellites and contributes to preparations for future missions.